3D Visualization of Document Retrieval Spaces Using VRML - Nelson, Michael J. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
With the advent of more powerful workstations on the Internet capable of fast graphical displays, the possibility of using a three dimensional visualization of a database of documents is greater than ever before. Much previous work on the visualization of documents has concentrated on the two dimensional representation of document spaces.